2017
DOI: 10.1039/c7dt00058h
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically recoverable Fe3O4@Au-coated nanoscale catalysts for the A3-coupling reaction

Abstract: The utility of novel Fe 3 O 4 @Au nanoparticles as magnetically separable and recyclable heterogeneous catalysts for the A 3 -coupling reaction of aldehydes, amines and terminal alkynes to yield the corresponding propargylamines is demonstrated. Herein we present a comprehensive analysis of the experimentally observed trends in the conversions with computational analysis using LUMO density on molecular isosurfaces and the electrostatic potential (ESP) effects estimated using DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Different research teams have reported the immobilization of Au NPs on the magnetic NPs and their application in the three‐component coupling reactions with types of composite materials because of their ability to activate the alkyne C−H bonds. For example, Iyer and co‐workers have reported a convenient method for the preparation of Fe 3 O 4 nanoparticle core coated with gold NPs (Fe 3 O 4 @Au NPs) as a new catalyst . Fe 3 O 4 @Au NPs catalyzed A 3 coupling reaction of aldehydes with amines and terminal alkynes to give the corresponding propargylamines in the absence in toluene at 100 °C without using inert atmosphere, special additives or base under mild reaction conditions (Scheme ).…”
Section: The Various Catalytic Systems For A3 Coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different research teams have reported the immobilization of Au NPs on the magnetic NPs and their application in the three‐component coupling reactions with types of composite materials because of their ability to activate the alkyne C−H bonds. For example, Iyer and co‐workers have reported a convenient method for the preparation of Fe 3 O 4 nanoparticle core coated with gold NPs (Fe 3 O 4 @Au NPs) as a new catalyst . Fe 3 O 4 @Au NPs catalyzed A 3 coupling reaction of aldehydes with amines and terminal alkynes to give the corresponding propargylamines in the absence in toluene at 100 °C without using inert atmosphere, special additives or base under mild reaction conditions (Scheme ).…”
Section: The Various Catalytic Systems For A3 Coupling Reactionsmentioning
confidence: 99%
“…It is important to stress that despite huge advancements of the reported works in the literature, another important challenges in the A 3 coupling reactions is nature of solvent and kind of the catalyst. A number of nanocatalysts, including copper, silver, gold, nickel, magnetic nanocatalysts and Co 3 O 4 , ZnS and nanopowder zinc titanate were successfully applied for A 3 coupling reactions with yields ranging from good to excellent in appropriate times in organic solvents or aqueous medium . The authors ascribed high catalytic activity of nanocatalysts to the particles size.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…The NiO/OA‐CuFe 2 O 4 nanocatalyst was employed in an inexpensive and economical protocol for the A 3 ‐coupling reaction of aldehydes, amines, and terminal alkynes. The proposed procedure was very easy, and involved many advantages such as (I) using Ni, Cu, and Fe low‐cost species instead of Pd and other precious metals such as Au and Ag, (II) good to excellent activity in the A 3 ‐coupling reaction along with the resonable selectivity, (III) easy work‐up procedure, (IV) no need to any co‐catalyst or activator in the catalytic reaction, and (V) being applicable to a wide range of substituated starting materials for synthesis of the corresponding propargylamine products with good to excellent yields. The NiO/OA‐CuFe 2 O 4 nanocatalyst could effectively be recycled up to five consecutive runs.…”
Section: Discussionmentioning
confidence: 99%
“…These coupling reactions proceed in the presence of a catalyst such as gold, zinc, copper, silver, iron‐based catalysts . Recently, development of novel and efficient catalysts for promoting KA 2 and A 3 coupling reactions received growing attention and various catalysts including magnetic catalysts such as Fe 3 O 4 @Au nanoparticles, magnetically separable CuO nanoparticles supported on graphene oxide, Cu 2 O/nano‐CuFe 2 O 4 and hybrid catalysts such as Cu(II) Schiff base complex immobilized on graphene oxide, sulfonate‐based Cu(I) metal–organic frameworks, copper nanoparticles supported on starch micro particles, have been reported . Similarly, tetrazoles are one of the most significant intermediates used for the synthesis of more complicated compounds.…”
Section: Introductionmentioning
confidence: 99%